Raised to Rule : Educating Royalty at the Court of the Spanish Habsburgs, 1601-1634 - Hoffman, Martha K., 1963- (Book collections on Project MUSE., 2011)
The children of Philip III of Spain (1578û1621) and Margarita de Austria (1584û1611) inherited great potential power: the abilities to declare war or make peace, to advocate religious doctrine, and to exert lasting influence over art, culture, and taste. The leadership provided by this generation raises the question of how royal families learned the roles they played in court, country, and on the international stage. In Raised to Rule, Hoffman presents a deeply researched and stimulating study of the formative experiences of children in the royal households of early modern Spain. Five of the e.